2006
DOI: 10.1210/en.2005-0654
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Mice Expressing P450 Aromatase as a Model for Male Infertility Associated with Chronic Inflammation in the Testis

Abstract: Our previous studies have shown that transgenic male mice expressing human P450 aromatase (AROM+) are infertile. In the present study, we followed the testis phenotype up to 15 months of age in these mice. The testes of the old AROM+ mice showed Leydig cell hypertrophy and hyperplasia, as indicated by the staining for steroidogenic enzymes and androgen and estrogen receptors. However, the Leydig cell adenomas did not show signs of malignization. In contrast, we observed a marked increase in the number of activ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
94
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 69 publications
(101 citation statements)
references
References 53 publications
7
94
0
Order By: Relevance
“…At 9 mo there was a notable reduction in the numbers of all germ cell types and by 15 mo the seminiferous tubules were atrophic and nearly all germ cell populations were depleted. 67 Giant multinucleated cells were present in the interstitium of all age groups and immunohistochemical analysis revealed that these cells were in fact macrophages, and increased in number with increasing age. 67 Given the fact that intratesticular estradiol concentrations also increased with age in these mice, it is likely that the surge in aromatization is indirectly exacerbating the testicular phenotype as the effect of heightened estradiol levels on the testis have been well documented.…”
Section: Arommentioning
confidence: 94%
See 1 more Smart Citation
“…At 9 mo there was a notable reduction in the numbers of all germ cell types and by 15 mo the seminiferous tubules were atrophic and nearly all germ cell populations were depleted. 67 Giant multinucleated cells were present in the interstitium of all age groups and immunohistochemical analysis revealed that these cells were in fact macrophages, and increased in number with increasing age. 67 Given the fact that intratesticular estradiol concentrations also increased with age in these mice, it is likely that the surge in aromatization is indirectly exacerbating the testicular phenotype as the effect of heightened estradiol levels on the testis have been well documented.…”
Section: Arommentioning
confidence: 94%
“…The AROM + male phenotype was followed up at 9 and 15 mo of age, and in some instances in both age groups Leydig cell adenomas were present, however no malignant or metastatic tumors were observed. 67 Interestingly, spermatogenic disruption worsened with age. At 9 mo there was a notable reduction in the numbers of all germ cell types and by 15 mo the seminiferous tubules were atrophic and nearly all germ cell populations were depleted.…”
Section: Arommentioning
confidence: 99%
“…In contrast to the muscle cell hyperplasia frequently observed in BOO, 40,41 the detrusor in AROMϩ/6J mice undergoes atrophy at 10 months of age. Similarly to AROMϩ/N males, 29,35 the AROMϩ/6J males showed high serum E 2 and low testosterone levels, decreased androgen/estrogen ratio, and disrupted reproductive development and spermatogenesis, putatively due to estrogen susceptibility of the C57Bl/6J genetic background. 28 Androgen receptor has been detected in bladder detrusor, 42 and muscle cells showed androgen response.…”
Section: Discussionmentioning
confidence: 90%
“…29 The small testes of the 10-month-old AROMϩ/6J males had a phenotype identical to that previously described in AROMϩ/N mice, including macrophage activation, Leydig cell depletion, dysmorphic seminiferous tubules, and disrupted spermatogenesis. 29,35 In contrast to the males, no major phenotypic alterations were found in the AROMϩ/6J females, and they presented with normal fertility with normal pregnancies, pup delivery, litter size, nursing, and offspring development. Macroscopically, the prostates of the 10-month-old AROMϩ/6J males were significantly smaller, compared with WT males.…”
Section: Cyp19a1-overexpressing Mice In the C57bl/ 6j Genetic Backgromentioning
confidence: 95%
“…Because we found no regression of seminal vesicles in young mice, the cause of infertility had to be further investigated. In females, AhR plays a critical role in fertility by directly regulating aromatase gene (Cyp19) expression (10), but in males, overexpression of Cyp19 is associated with low fertility (12). We investigated whether the expression level of aromatase is affected by depletion of AhR in male mice.…”
Section: Low Fertility Of Young Ahr-deficient Male Mice With No Changmentioning
confidence: 99%